Rumah Ibadah Sebagai Sarana Alternatif Penunjang Kebutuhan Dasar Masyarakat - Aam Alamsyah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
welfare of the people. As one of the most populous contries, Indonesia still faces serious problem in water management and good sanitation. Particularly, in big cities, with the unequal spread of the residents and the soaring prices of the land, good sanitation is a classical problem, which remains unrevolvable until now. This article constitutes a review that aims to highlight the role of praying facilities, which can possibly be used as an alternative facility to support the government program in providing clean water and good sanitation to the surrounding communities. The use of praying facilities in providing water and good sanitation will not only impact to the health and the economy of the surrounding socieites but also increase the role of the praying facilities as the pioneer of the social piety, which is useful to help solve the nation’s problem, particularly in helping the people to fulfill their basic needs